2017
DOI: 10.1002/cncr.31196
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus stereotactic body radiation therapy for stage I non–small cell lung cancer: A comprehensive review

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death in the United States. With the implementation of lung cancer screening, the number and proportion of patients diagnosed with early-stage disease are anticipated to increase. Surgery is currently the standard of care for patients with operable stage I NSCLC. However, promising outcomes with stereotactic body radiation therapy (SBRT) in patients with inoperable disease has led to interest in directly comparing SBRT and surgery in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 71 publications
(202 reference statements)
0
105
0
3
Order By: Relevance
“…In addition, lymph node metastasis is rare, like it is in patients with T1 NSCLC. A growing number of T1N0 NSCLC patients are nowadays treated with stereotactic body radiation (SBRT) [60,61]. In these patients surgical lymph node staging, like in EBT for carcinoid, is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lymph node metastasis is rare, like it is in patients with T1 NSCLC. A growing number of T1N0 NSCLC patients are nowadays treated with stereotactic body radiation (SBRT) [60,61]. In these patients surgical lymph node staging, like in EBT for carcinoid, is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we could not project the demand for targeted or immunotherapy agents because these are very recent developments. Furthermore, although current guidelines recommend stereotactic body radiotherapy only for patients with medically inoperable early‐stage NSCLC, there is an ongoing debate on its appropriateness in operable patients . Therefore, the proportion of early‐stage cases that require radiotherapy could increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although current guidelines recommend stereotactic body radiotherapy only for patients with medically inoperable early-stage NSCLC, 6 there is an ongoing debate on its appropriateness in operable patients. 30,31 Therefore, the proportion of early-stage cases that require radiotherapy could increase in the future. Two other developments that may possibly alter our estimates are the introduction of risk models to select individuals for screening and the use of nodule management strategies such as Lung-RADS.…”
Section: Limitationsmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) is an alternative treatment option to surgery for patients with stage I NSCLC, especially those who have medical comorbidities that preclude surgery. Phase 2 trials of early NSCLC report local control rates from 85% to 92% and OS rates from 43% to 60% at 3 years . Two randomized phase 3 trials of SBRT versus surgery for operable stage I NSCLC are currently recruiting.…”
Section: Non–small Cell Lung Cancermentioning
confidence: 99%
“…Phase 2 trials of early NSCLC report local control rates from 85% to 92% and OS rates from 43% to 60% at 3 years. 75 LRR after surgery for NSCLC primarily occurs in 2 peaks: the first at 6 to 8 months and the second at 22 to 24 months. 77 An analysis of 74 patients who developed a local recurrence after surgery for stage I NSCLC reported that patients who underwent surgical re-resection survived significantly longer than those who received chemotherapy or radiotherapy, although the 5-year postrecurrence survival rate after repeat surgery remained dismal at only 15%.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%